Integrated business continuity and disaster recovery planning: Towards organizational resilience - Sahebjamnia, N.; Torabi, S.A.; Mansouri, S.A. (European journal of operational research, 2015)
Businesses are increasingly subject to disruptions. It is almost impossible to predict their nature, time and extent. Therefore, organizations need a proactive approach equipped with a decision support framework to protect themselves against the outcomes of disruptive events. In this paper, a novel framework is proposed for integrated business continuity and disaster recovery planning for efficient and effective resuming and recovering of critical operations after being disrupted. The proposed model addresses decision problems at all strategic, tactical and operational levels. At the strategic level, the context of the organization is first explored and the main features of the organizational resilience are recognized. Then, a new multi-objective mixed integer linear programming model is formulated to allocate internal and external resources to both resuming and recovery plans simultaneously. The model aims to control the loss of resilience by maximizing recovery point and minimizing recovery time objectives. Finally, at the operational level, hypothetical disruptive events are examined to evaluate the applicability of the plans. We also develop a novel interactive augmented ε-constraint method to find the final preferred compromise solution. The proposed model and solution method are finally validated through a real case study. •Proposing a new conceptual framework for IBCDRP.•Formulating a novel resource allocation model for IBCDRP framework.•Developing a novel interactive augmented ε-constraint method.•Validating the proposed model and solution technique via a real case study.